(3GdEJLGgGJ GdMOjKI GdMOjKI aj GdJMdjd GdfbOj (B/s - (3eYJhb,SgjQ eMehO s ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 1977)
(3jJYQV gPG GdcJGH HGdOQGSI h GdJMdjd ddEJLGgGJ GdMOjKI aj GdJMdjd GdfbOj eQcRG Ydi Jdc GdJWhQGJ GdJj MOKJ aj OQGSI GKQ GdJZjQ aj cejI GdfbhO Ydi eNJda GdXhGgQ GdEbJUGOjI h HGdPGJ Ydi eSJhi GdGSYGQ h eSJhi GdONd h GdJTZjds
Keywords: (3GdCQUOI GdfbOjIs; (3GdESJKeGQs; (3GdacQ Gdcejs